PERWATAKAN TOKOH DALAM NOVEL MARIPOSA KARYA LULUK HF - Fitriani, Rahma; Priyadi, Antonius Totok; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study examines the characters in the novel Mariposa by Luluk HF, and to describe character analytically, character dramatically; and thatis to decribe implementation of the results into the Indonesian intructions at school. The benefit of this study are devide into two categories: practical and theoritical. This psychological analysis study was conducted by referring to Albertine Minderop's theory. This study using descriptive methods and psychoanalysis approach. The data sources in this research is Mariposa novel, while the data are words, phrases and expressions. The data collection in this study uses documentary study technique. Data collections tool in this study is direct research as a key instrument. The analysis shows that 1) the analytic character of the Mariposa novel by Luluk HF. 2) Mariposa's dramatic character novel by Luluk HF. 3) The results are implemented into Indonesian language and art subject matter in basic competencies 3,9 and 4,9 from third grade in high school.Â Keywords: Character, Psychology, novel